Analisis Perbandingan File Carving Recuva, PhotoRec, dan FTK Imager pada Flashdisk - Mumtaz Imanullah; Eryal Rivano Zistafa; Yustian Servanda (Nolsatu Publisher, 2026)
Recovering deleted data from flash drives has become a crucial requirement in digital forensics and personal data recovery. This study compares file carving and metadata-based file recovery techniques across three applications: Recuva, PhotoRec, and FTK Imager. Fifty files of various types permanently deleted from an 8GB FAT32-formatted flash drive were tested sequentially across the three applications. Evaluation parameters included the number of recovered files, integrity through hash verification, percentage of openable files, ability to preserve original names, and scanning speed. Recuva's deep scan feature excelled in recovering metadata, including file names and folder hierarchies. PhotoRec achieved the highest recovery volume thanks to its aggressive header and footer detection, but was unable to preserve file names or directory structures. FTK Imager achieved the highest file integrity with the most stable recovery, despite requiring a longer scan time. This study confirms that no application excels in all aspects, so tool selection should be tailored to user priorities.